2020
DOI: 10.38124/ijisrt20sep503
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Port Scanner

Abstract: In a computer network, an attack is an attempt to destroy or steal unauthorized information or make use of information as an asset. One of the attacks is a reconnaissance attack considered as the first step of a computer attack. This type of attack is mostly done by a black hat, an expert in the programmer, by scanning the internal network devices and gather vulnerability information. In this paper, shows the identification of open ports and services through the network and available IP on the network are poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The methods of computer network cybersecurity analysis were studied and it was found that one of the basic and mandatory methods of any security analysis is the method based on scanning the ports of devices connected to the local network. It is used both in computer networks [1][2][3] and in computer-integrated systems, in particular IoT systems [4][5][6] and smart home systems [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of computer network cybersecurity analysis were studied and it was found that one of the basic and mandatory methods of any security analysis is the method based on scanning the ports of devices connected to the local network. It is used both in computer networks [1][2][3] and in computer-integrated systems, in particular IoT systems [4][5][6] and smart home systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hackers also use it to identify network services running on the host and search for vulnerabilities. There are two types of port scanning [1][2][3]:…”
Section: Introductionmentioning
confidence: 99%